DEVELOPMENT OF LEARNING DEVICES (DEMO SET) FOR INTEGRATED PROCESS CONTROL SYSTEMS - Alfriza Faiz, Rio
A control system is needed in the process industry to keep the process running safely and yield the product as desired. This control system integrates various devices such as instrumens, PLC, OPC and HMI. These devices communicate with each other to perform control functions. The most commonly used control in the process industry is the PID controller. The control performance of the PID controller depends on the PID parameter given, if the parameter value is not suitable then the process can become unstable and endanger the plant. Therefore the PID parameters need to be simulated before they are implemented in the actual process. In this final project, a demo set will be created that integrates various devices, that is PLC, OPC, HMI and simulation devices such as process control systems in the industrial world. In this final project, a dry tank emulator in the form of an electric circuit is created to represent a multi tank interacting system based on the modeling obtained from the bond graph method. Demo set was successfully created by integrating dry tank emulators, PLC, OPC, HMI and simulation devices using MATLAB. The simulation results show that the model created has been able to represent the actual system that is a dry tank emulator based on the mean absolute rrror value that is lower than 3%. It is expected that this demo set can be used as a learning equipment to study PLCs, OPCs, HMIs, data communications, PID controllers, MATLAB simulations, multi tank system dynamics and integration of all these devices.